Historical development of tourism in Serbia - Krejić, Živana; Čerović, Slobodan; Milićević, Snežana (Hotel and Tourism Management, 2017)
The analysis of the research papers on the beginnings of tourism development in the world led to the conclusion that our literature lacked detailed studies dealing with the historical development of tourism in Serbia. The aim of this paper is to present the results of the research into the available documentation on the developments related to the first forms and types of tourism, including observations, notes and experiences of the first passengers on the territory of today’s Serbia. In order to indicate the directions of the current tourism development, it is necessary to analyse its original forms in the past, and also to compare whether the first tourism forms have reached their peak development until today. The importance of tourism can be seen not only through its economic indicators and impacts, but also through cultural, educational, health and other needs of both tourists and locals. Various forms of tourism in the past can affect not only their future development, but also the tourist consumption of domestic and foreign tourists, as well as the development of the entire tourism industry.